The circles of life (5) Today's innovations tomorrow's traditions - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The circles of life (5) Today's innovations tomorrow's traditionsDo not despair. Necessity is the mother of invention. We just have to open our minds to the possibilities we have to create. Tucked away in a report of the 1996 World Food Summit is a...